Comparison of diagnostic accuracy of root perforation, external resorption and fractures using cone-beam computed tomography, panoramic radiography and conventional & digital periapical radiography - Wilton Mitsunari Takeshita; Mariliani Chicarelli; Lilian Cristina Vessoni Iwaki (Wolters Kluwer Medknow Publications, 2015)
Context: Some radicular changes are challenging for clinicians to diagnose, such as of root perforations, external root resorption (ERR), and vertical root fractures (VRFs). This study aims to facilitate it by comparing the diagnostic accuracy of cone-beam computed tomography (CBCT), orthopantomography, and conventional and digital periapical radiography (DPR) in the diagnosis of such problems. Is it worth doing CBCT despite the radiation dose? Aims: To evaluate and compare the diagnostic accuracy of CBCT, panoramic radiography, and conventional and DPR in the diagnosis of root perforation (RP), ERR, and VRF. Materials and Methods: The sample consisted of 40 extracted human teeth and 10 macerated human mandibles. RPs were performed using diamond burs, ERRs using spherical carbide burs, and RFs using a universal machine EMIC-DL 1000. The images were evaluated by 6 dentomaxillofacial radiologists. Results: Receiver operating characteristic (ROC) revealed that CBCT showed the highest area under the ROC curve (Az) values for RP, ERR, and VRF (0.903, 0.950, and 0.849, respectively). The worst Az values for RP, ERR, and VRF (0.718, 0.494, and 0.611, respectively) were for panoramic radiography. Conclusions: CBCT showed the best results in the diagnosis of ERR and VRF. The diagnosis of ERR was the least accurate, panoramic radiography being not appropriate for its diagnosis. CBCT and conventional periapical radiography obtained similar results for the evaluation of RP. So for, RP indicate the conventional periapical radiography because CBCT has a higher radiation dose.